Preliminary Investigation on Vertical Distribution of Phytoplankton Biomass and Nutrients in Tasik Biru (Blue Lake), Bau, Sarawak. - Harith, Mohd Nasarudin; Hassan, Ruhana (2008)
Located in Bau district, Sarawak, Tasik Biru, formed from an open cast gold mining pit, was opened to the public as recreational area in 2001. Due to the gold mining activities, the water contains high content of arsenic as declared by Natural Resources and Environmental Board (NREB) of Sarawak. Therefore, this study served as a baseline data on determining the fertility of the lake in terms of phytoplankton biomass composition. The study was carried out in seven months period (May -November 2007). Water samples were taken from three different depth namely subsurface, middle and bottom layers at the shallow side of the lake for determination of chlorophyll a concentration. Besides that, the nutrient analyses namely orthophosphate, nitrate and ammonia were also conducted to observe their relationship with phytoplankton biomass. Tasik Biru was categorized as oligotrophic lake based on the range of the chlorophyll a concentration in the sampling period (0.6831 IJ.g/t to 3.1047 IJ.g/f).